KEARIFAN LOKAL SEBAGAI MEDIA PENANAMAN KARAKTER SOSIAL DAN LITERASI SAINS ANAK USIA DINI: KAJIAN LITERATUR SISTEMATIS - Sarina; Indah Kristiani Siringo Ringo; Maronta, Yusuf; Arif Wicaksono, Muhammad; Annisa Akbar, Ayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early childhood education (ECE) plays a fundamental role in shaping children's personality and moral foundations, yet the implementation of character education in practice still faces various obstacles due to approaches that tend to be general and less contextual. Meanwhile, the demand for early science literacy is increasingly urgent in the era of globalization, but the ECE curriculum has not yet integrated scientific concepts with culture and environment in an applicable manner. This study aims to synthesize findings regarding the potential of local wisdom as a medium for instilling social character and science literacy in early childhood through a systematic literature review. The method employed is a systematic literature review (SLR) following the PRISMA protocol, which consists of four main stages: identification, screening, eligibility, and inclusion. Literature searches were conducted on reputable academic databases including Scopus, Web of Science, ERIC, and Google Scholar with publication range from 2020 to 2026, using keywords such as